Evaluation of DMEK with secondary IOL implantation in cases of aphakic bullous keratopathy - Amr S Galal; Moumen M Seleet; Mohamed A Kabeel; Ayman H Swar (Journal of the Egyptian Ophthalmological Society, 2023)
Context DMEK is used to treat corneal decompensation. This study focuses on the succcess and outcome of DMEK with and without secondary IOL implantation. Aims The purpose of our work is to evaluate Descemet membrane endothelial keratoplasty (DMEK) with secondary Intraocular lens (IOL) implantation in cases of aphakic bullous keratopathy with insufficient capsular support. Settings and design Pilot study. Methods and material This was a nonrandomized comparative prospective interventional case series where 11 eyes of 11 patients with aphakic bullous keratopathy secondary to complicated cataract surgery underwent DMEK with secondary IOL implantation using modified Yamane technique, and results were compared to 11 eyes of 11 patients underwent DMEK only. Statistical analysis used The statistical analysis was conducted using the Statistical Package for Social Sciences (SPSS 15.0.1 for windows; SPSS Inc, Chicago, IL, 2001). Results Both groups showed a high success rate (81.8%) with rebubbling required in 3 eyes in both groups. Both groups also showed significantly improved BCVA, decreased CCT and a decrease in donor graft ECD. Conclusions DMEK combined with secondary IOL implantation by modified Yamane technique appears to be a feasible method in managing aphakic bullos keratopathy with inadequate capsular support, and results are comparable to DMEK alone.